Determination of antibacterial and antioxidant potential of organic crude extracts from Malus domestica, Cinnamomum verum and Trachyspermum ammi - Asma Irshad; Rabbia Jawad; Qudsia Mushtaq; Alexis Spalletta; Patrick Martin; Uzair Ishtiaq (Scientific Reports)
Abstract Plants are the rich source of biologically active compounds which can be obliging against various pathogenic microorganisms and cancerous diseases. The current study evaluated the antibacterial potential of aqueous, methanol, ethanol, and acetone extracts of Malus domestica (apple), Cinnamomum verum (cinnamon) and Trachyspermum ammi (ajwain) via agar well diffusion methods and minimum inhibitory concentration (MIC) in (mm) against Staphylococcus aureus (ATCC 25923) and Salmonella typhi (ATCC 19430). The antioxidant properties including total phenolic content (TPC), total flavonoid content (TFC), DPPH and reducing power was determined by UV/VIS spectrophotometery and all the results interpreted through one way ANOVA (STATISTICA). In the results, methanolic and acetonic extracts of C. verum has shown maximum zone of inhibition (22.3 ± 0.58 mm) against S. aureus while for C. verum and T. ammi, ethanolic extracts has expressed the maximum zone of inhibition (22.3 ± 0.58 mm) against S. typhi and for M. domestica the methanolic extracts has exhibited highest zone of inhibition (18 ± 0.56 mm) among all other extracts of M. domestica. The MIC values were comparable with antimicrobial activity. Among the antioxidant activity analysis, the highest level of TPC has observed in aqueous extract of M. domestica 72.15 ± 1.80 mg GAE/g, while highest TFC was observed in methanolic extracts of M. domestica 15.62 ± 0.25 µg CE/g. The DPPH assay showed maximum percentage inhibition 123% in the methanolic extract of M. domestica, while highest reducing potential 13.42 ± 1.15 nm was observed in aqueous extract of C. verum. This study has compared three potential medicinal plants with biological active and eco-friendly components which play crucial role in therapeutics.